The Effect of Trust and Job Satisfaction on Citizenship Organizational Behavior in High school - Amini Amini; Isthifa Kemal (STAI Hubbulwathan Duri, 2021)
This research aims to understand the effect of trust and job satisfaction on organizational citizenship behavior. It was quantitative research in twenty-two senior high schools in Medan city, Sumatera Utara, Indonesia. The research used a survey method with path analysis applied in the testing hypothesis. It was conducted on 292 teachers as the respondents who were selected in a simple random way. The results of this study are: (1) There is a positive direct effect of trust on organizational citizenship behavior. (2) There is a positive direct effect of job satisfaction on organizational citizenship behavior, and (3) There is a positive direct effect of trust on job satisfaction.